'Ilmu al-Nahwi 'Inda Ilmi Bashoroh - Novita Rahmi (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
Nahwu0T 0T is a0T 0T principle0T 0T element of0T 0T Arabic. This discipline emerged in the early0T 0T time of Islam for preserving the pristine Arabic; because the encounter of Arab people and non-Arab 0T 0T unavoidably threatened the “pure” Arabic. There are two schools of Nahwu: school of Kufah and school of Bashrah. This article, however, will only0T 0T discuss the0T characteristics of Nahwu from 0T School0T of 0T Basrah’s perspective.0T